Method for preparing high-purity zinc and synergistically electrooxidizing ferrous ions and organic matters in zinc sulfate solution
Through diaphragm electrooxidation technology in the wet zinc smelting process, the problems of ferrous ions and organic matter oxidation are solved, and the preparation of high-purity zinc and the efficiency of zinc electrocalization process are improved.
Patent Information
- Application Number
- CN202510020335.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-03-28
AI Technical Summary
During the wet zinc smelting process, the oxidation of ferrous ions in the zinc oxide powder leaching solution leads to high production costs, and organic matter enters the zinc electrolyte, resulting in plate burning and low electric efficiency during the zinc electrostatic accumulation process.
Using diaphragm electrodistribution technology, electrodistribution is performed by direct current, so that the ferrous ions in the anode region are electrooxidized into trivalent ions, and the organic matter is electrooxidized and degraded into CO2 and H2O to obtain a zinc sulfate solution containing trivalent iron, and high-purity zinc is obtained in the cathode region.
It reduces production costs, improves economic benefits, solves the problems of ferrous ion oxidation and organic degradation, obtains high-purity zinc, and improves the current efficiency of zinc electrodistribution.
Smart Images

Figure CN119710274A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing high-purity zinc and coordinating electro-oxidation of ferrous ions and organic matter in a zinc sulfate solution, belonging to the technical field of hydrometallurgy. Background Art
[0002] At present, more than 85% of zinc is produced by wet zinc smelting, which is divided into three categories: conventional leaching, hot acid leaching and direct leaching of zinc sulfide concentrate. Conventional leaching wet zinc smelting accounts for more than 80% of the entire wet zinc smelting, which includes roasting of zinc sulfide concentrate, medium leaching, low acid leaching, leaching slag fire reduction volatilization to produce secondary zinc oxide powder, secondary zinc oxide powder leaching, leachate purification and electrolysis. One of the main problems is that the iron in the leachate after the secondary zinc oxide powder is leached is almost all ferrous ions, and a large amount of oxidants (such as hydrogen peroxide, etc.) are required to oxidize it into trivalent iron ions and then precipitate iron to achieve zinc and iron separation, and the production cost is very high. In addition, the secondary zinc oxide powder produced by fire reduction volatilization of zinc-containing materials such as steel smoke and lead smelting slag also contains a large amount of ferrous ions in its leachate, and the aforementioned problem of ferrous ion oxidation also exists, which needs to be solved urgently.
[0003] Secondary zinc oxide powder usually contains rare metals such as indium, germanium, and gallium, and has important recycling value. When secondary zinc oxide powder is leached, indium, germanium, gallium, etc. enter the leaching solution, which usually uses organic solvents to extract and separate indium, germanium, gallium or tannic acid / hydroxamic acid to precipitate germanium. This process will cause organic matter such as extractants, kerosene, tannic acid, and hydroxamic acid to enter the zinc electrolyte, and finally lead to problems such as plate burning, zinc re-dissolution, long dendrites, low electrical efficiency, and high power consumption during the zinc electrowinning process, which seriously endangers zinc production. In addition, when zinc sulfide concentrate is directly leached, organic matter in the flotation zinc concentrate process will also enter the zinc electrolyte, which will also cause the aforementioned problems in the zinc electrowinning process, which also need to be solved urgently.
[0004] At the same time, the main problems in the zinc electrolysis process are: (1) The lead-based anode reaction is mainly a water decomposition reaction, and the oxygen evolution potential is relatively high (about 1.73V), which leads to a high cell voltage, that is, high energy consumption for electrolysis; (2) The O2 released by the lead-based anode cannot be used. Not only is it wasted, but it also absorbs acid and water and escapes from the electrolytic cell to form acid mist, which corrodes equipment, deteriorates working conditions, and pollutes the environment; (3) The lead-containing anode mud generated during zinc electrolysis and trace lead ions in the electrolyte are either entrained or deposited in the cathode zinc sheet, resulting in excessive lead in the zinc sheet, which is one of the main reasons for the low quality of the zinc sheet; (4) Multivalent ions such as iron and manganese are continuously reduced and oxidized between the anode and cathode, reducing the current efficiency. Summary of the invention
[0005] In view of the serious problems of ferrous ion oxidation and zinc electrowinning in the above-mentioned wet zinc smelting, the present invention provides a method for preparing high-purity zinc and synergistically electro-oxidizing ferrous ions and organic matter in a zinc sulfate solution, wherein an anolyte containing ferrous ions and organic matter R is used as an anolyte in the anode area of a diaphragm electrolytic cell, a qualified zinc sulfate-sulfuric acid-water solution is selected as a catholyte, and a mixture of gelatin or bone glue and sodium petroleum sulfonate RSO3Na is added; direct current is passed through for electrowinning to electro-oxidize the ferrous ions in the anolyte in the anode area. The organic matter R is electro-oxidized and degraded into CO2 and H2O, and a zinc sulfate-sulfuric acid-water solution containing trivalent iron is obtained, and high-purity zinc and cathode electrolysis waste liquid are obtained in the cathode area; the anode mud of the anode is cleaned regularly and the cathode is stripped of zinc, and the zinc sulfate-sulfuric acid-water solution containing trivalent iron in the anode area is sent to the precipitation and iron removal process for iron removal; part of the cathode electrolysis waste liquid is sent to the wet zinc smelting leaching process, and the remaining part is cooled and mixed with a qualified zinc sulfate-sulfuric acid-water solution and then loaded into the cathode area as a new cathode electrolyte. The present invention can not only obtain high-purity zinc and solve the problems existing in zinc electrolysis, but also electro-oxidize ferrous ions in zinc sulfate solution and degrade organic matter.
[0006] A method for preparing high-purity zinc and synergistically electro-oxidizing ferrous ions and organic matter in a zinc sulfate solution, the specific steps are as follows: (1) loading an anode and an anolyte into the anode region of a diaphragm electrolyzer, and loading a cathode and a catholyte into the cathode region of the diaphragm electrolyzer; the anolyte is a zinc sulfate-sulfuric acid-water solution containing ferrous ions and organic matter R, and the catholyte is a mixture of gelatin or bone glue and sodium petroleum sulfonate RSO3Na added to a qualified zinc sulfate-sulfuric acid-water solution; (2) connecting the anode and cathode to the positive and negative electrodes of a DC power supply, respectively, and passing DC current for electrolysis, so that the ferrous ions in the anolyte of the anode area are electro-oxidized into ferric ions, and the organic matter R is electro-oxidized and degraded into CO2 and H2O, thereby obtaining a zinc sulfate-sulfuric acid-water solution containing ferric ions, and obtaining high-purity zinc and cathode electrolysis waste liquid in the cathode area; (3) Regularly remove the anode with anode mud from the anode area of the diaphragm electrolytic cell, and remove the cathode with high-purity zinc deposited from the cathode area, and reinstall the anode after cleaning the anode mud and the cathode after stripping the zinc into the anode area and cathode area of the diaphragm electrolytic cell respectively; (4) The zinc sulfate-sulfuric acid-water solution containing trivalent iron ions in the anode area is sent to the precipitation and iron removal step for iron removal; the cathode electrodeposition waste liquid is sent to the wet zinc smelting leaching step, and the remaining part is cooled and mixed with the qualified zinc sulfate-sulfuric acid-water solution in step (1) and then loaded into the cathode area of the diaphragm electrolytic cell as a new cathode electrolyte.
[0007] Preferably, the anode electrolyte in step (1) contains 0.02-25 g / L ferrous ions, 20-180 g / L zinc ions, 0.02-50 g / L sulfuric acid, 30-5000 mg / L total organic carbon (OR), and trace amounts of other metal ions and non-metal ions.
[0008] Preferably, the cathode electrolyte in step (1) contains 30-80 g / L zinc ions, 90-210 g / L H2SO4, 2-8 g / L Mn and trace impurity ions, wherein the trace impurity ions are Cu≤2 mg / L, Cd≤3 mg / L, Ni≤2 mg / L, Co≤2 mg / L, As≤3 mg / L, Sb≤0.5 mg / L, Ge≤0.05 mg / L, Fe≤20 mg / L, F≤100 mg / L, and Cl≤250 mg / L; and based on the amount of Zn produced, the amount of the mixture of gelatin or bone glue and sodium petroleum sulfonate RSO3Na added is 0.03-0.5 kg / t.
[0009] Preferably, in step (1), the anode is a lead-based alloy plate, and the cathode is a pure aluminum plate.
[0010] Preferably, the diaphragm electrolyzer in step (1) is composed of an anode region, a diaphragm and a cathode region which are arranged in parallel with each other, and the diaphragm is an anion exchange membrane or a proton exchange membrane.
[0011] Preferably, the current density of the electrolytic deposition in step (2) is 300-600 A / m 2 , temperature is 30~50℃, time is 24~48h.
[0012] Preferably, in the step (2), the ferrous ion content of the zinc sulfate-sulfuric acid-water solution containing trivalent iron is less than 10 mg / L, the total organic carbon of the organic matter R is less than 15 mg / L, the mass concentration ratio of H2SO4 to zinc ion in the cathode electrolysis waste liquid is 2-5:1, and the zinc ion content in the cathode electrolysis waste liquid at the end point of electrolysis is 1.5-15 g / L lower than the zinc ion content in the cathode electrolyte at the starting point.
[0013] Preferably, in step (3), the anode removal cycle is 4 to 7 days, and the cathode removal cycle is 24 to 48 hours.
[0014] Preferably, the precipitation iron removal method in step (4) is iron precipitation by hydrolysis or goethite precipitation.
[0015] Preferably, the volume fraction of the cathode electrodeposition waste liquid sent to the hydrometallurgical zinc leaching process in step (4) is 8% to 25%.
[0016] The principle of the method of the present invention is as follows: 1. During zinc electrolysis, the main reaction at the lead-based alloy anode is the electro-oxidation reaction of ferrous ions:
[0017] The present invention uses ferrous ion electrooxidation reaction to replace the water-oxygen decomposition reaction of conventional zinc electrowinning. The standard electrode potential of the reaction is 0.77 V, which is 0.96 V lower than the oxygen evolution potential (including oxygen evolution overpotential) of 1.73 V. Based on a current efficiency of 90%, the production of one ton of zinc can save 874.6 degrees of direct current power. At the same time, the large consumption of hydrogen peroxide and pyrolusite during the oxidation of ferrous ions in zinc sulfate solution in the conventional hydrometallurgical zinc smelting process is avoided, which can greatly save production costs and improve economic benefits. In addition, the method of the present invention can avoid the problem of acid mist polluting the environment caused by oxygen precipitation at the anode.
[0018] 2. When electroplating zinc, water molecules discharge to form Adsorbed on the lead-based alloy anode, i.e. , organic matter R and Reaction, at the same time, the organic matter R will also react with PbO2 on the surface of the lead-based alloy anode, the reaction is as follows, thereby degrading R into CO2 and H2O, avoiding the burning of the plate and the reduction of electrical efficiency caused by R during zinc electroplating.
[0019]
[0020]
[0021]
[0022] 3. During zinc electroplating, one of the side reactions that is prone to occur at the lead-based alloy anode is as follows:
[0023]
[0024]
[0025]
[0026] The above reaction is one of the main reasons for the low quality of zinc flakes produced by traditional hydrometallurgical zinc smelting. The present invention adopts diaphragm electrowinning, and anode mud, lead ions and other metal cations cannot migrate from the anode area to the cathode area, thereby improving the quality of electrolytic zinc, and the zinc content of the produced zinc is ≥99.999%.
[0027] 4. The cathode reaction of the present invention is Zn 2+ Reduction reaction: The present invention adopts diaphragm electrowinning, and the cathode reaction is mainly Zn 2+ The reduction reaction can avoid the situation in which multivalent ions such as iron and manganese are continuously reduced and oxidized between the anode and cathode during traditional zinc electrowinning, thereby improving the current efficiency.
[0028] The beneficial effects of the present invention are: (1) The main anode reaction of the present invention replaces the water-oxygen decomposition reaction of traditional zinc electrolysis with the electro-oxidation reaction of ferrous ions and the electro-oxidation degradation reaction of organic matter, and eliminates the separate ferrous ion oxidation process of traditional hydrometallurgical zinc smelting, thereby reducing production costs and improving economic benefits; at the same time, it solves the problem of acid mist pollution of the environment caused by oxygen precipitation at the anode in traditional hydrometallurgical zinc smelting; (2) The present invention can not only obtain high-purity zinc and solve the problems existing in zinc electrowinning, but also can electro-oxidize ferrous ions in zinc sulfate solution and degrade organic matter; it solves the common problems existing in traditional zinc electrowinning, such as low zinc sheet quality, low added value, high energy consumption, plate burning, low electrical efficiency, and high environmental pollution such as acid mist; (3) The present invention adopts diaphragm electrolysis, which avoids the continuous reduction and oxidation of multivalent ions such as iron and manganese between the anode and cathode in traditional zinc electrolysis, thereby improving the current efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a physical picture of high-purity zinc in Example 1; Figure 2 This is the XRD diagram of high purity zinc in Example 2; Figure 3 This is the SEM / EDS image of high-purity zinc in Example 3; Figure 4 This is the infrared spectrum of zinc sulfate-sulfuric acid-water solution after degradation of organic matter R in Example 4. DETAILED DESCRIPTION
[0030] The present invention is further described in detail below in conjunction with specific implementation modes, but the protection scope of the present invention is not limited to the described contents.
[0031] Example 1: A method for preparing high-purity zinc and synergistically electro-oxidizing ferrous ions and organic matter in a zinc sulfate solution, the specific steps are as follows: (1) The anode (lead-based alloy plate) and the anolyte are loaded into the anode area of a diaphragm electrolytic cell, and the cathode (pure aluminum plate) and the cathode electrolyte are loaded into the cathode area of a diaphragm electrolytic cell (the diaphragm electrolytic cell is composed of an anode area, a diaphragm and a cathode area arranged in parallel at intervals, and the diaphragm is an anion exchange membrane); the anolyte is a zinc sulfate-sulfuric acid-water solution containing ferrous ions and organic matter R, and the anolyte contains 0.02 g / L ferrous ions, 180.0 g / L zinc ions, 0.02 g / L sulfuric acid, 30 mg / L total organic carbon of organic matter R, trace amounts of other metal ions (Cu 0.2 g / L, Cd 0.6 g / L, Ni 0.01 g / L, Co 0.01 g / L, As 0.3 mg / L, Sb 0.3 mg / L) and non-metal ions (F 125 mg / L, Cl550mg / L); the cathode electrolyte is a mixture of gelatin and sodium petroleum sulfonate RSO3Na added to a qualified zinc sulfate-sulfuric acid-water solution (the mass ratio of gelatin to sodium petroleum sulfonate RSO3Na is 4:1), and the addition amount of the mixture of gelatin and sodium petroleum sulfonate RSO3Na is 0.5kg / t based on the output Zn amount; the cathode electrolyte contains zinc ions 80g / L, H2SO4 210g / L, Mn 8g / L and trace impurity ions, and the trace impurity ions include Cu≤2mg / L, Cd≤3mg / L, Ni≤2mg / L, Co≤2mg / L, As≤3mg / L, Sb≤0.5mg / L, Ge≤0.05mg / L, Fe≤20mg / L, F≤100mg / L, and Cl≤250mg / L; (2) The anode (lead-based alloy plate) and cathode (pure aluminum plate) are connected to the positive and negative electrodes of a DC power supply respectively, and a DC current is passed through the electrodeposition at a temperature of 50°C (the current density of the electrodeposition is 600A / m 2 ), the zinc ion content in the cathode electrolysis waste liquid at the end of electrolysis is 15g / L lower than the zinc ion content in the cathode electrolyte at the starting point, so that the ferrous ions in the anode electrolyte of the anode area are electro-oxidized into trivalent ferrous ions, and the organic matter R is electro-oxidized and degraded into CO2 and H2O, and a zinc sulfate-sulfuric acid-water solution containing trivalent ferrous ions is obtained (ferrous ions <10mg / L, total organic carbon of organic matter R <15mg / L), and high-purity zinc and cathode electrolysis waste liquid (the mass concentration ratio of H2SO4 to zinc ions is 3:1) are obtained at the cathode; (3) Regularly remove the anode with anode mud from the anode area of the diaphragm electrolytic cell (cycle is 4 days), remove the cathode with high-purity zinc deposited from the cathode area (cycle is 24 hours), and reinstall the anode after cleaning the anode mud and the cathode after stripping the zinc into the anode area and cathode area of the diaphragm electrolytic cell; (4) The zinc sulfate-sulfuric acid-water solution containing trivalent iron ions in the anode area is sent to the precipitation and iron removal process for neutralization and hydrolysis to remove iron; the cathode electrodeposition waste liquid with a volume fraction of 8% is sent to the hydrometallurgical zinc leaching process, and the remaining part is cooled and mixed with the qualified zinc sulfate-sulfuric acid-water solution in step (1) and then loaded into the cathode area of the diaphragm electrolytic cell as a new cathode electrolyte; The actual picture of high purity zinc in this embodiment is shown in Figure 1 ,from Figure 1 It can be seen that the zinc sheet has a smooth and dense surface, no dendrites, no traces of burning and zinc re-dissolution; Table 1 is a composition table of high-purity zinc.
[0032] Table 1 High purity zinc composition It can be seen from Table 1 that the purity of the high-purity zinc in this embodiment can reach 99.9994%; the ferrous ion oxidation rate in this embodiment is 76.3%, the organic matter degradation rate is 71.8%, the current efficiency is 92.5%, and the DC power consumption is 2925kW·h / t·Zn.
[0033] Example 2: A method for preparing high-purity zinc and synergistically electro-oxidizing ferrous ions and organic matter in a zinc sulfate solution, the specific steps are as follows: (1) An anode (lead-based alloy plate) and an anolyte are placed in the anode region of a diaphragm electrolytic cell, and a cathode (pure aluminum plate) and a cathode electrolyte are placed in the cathode region of a diaphragm electrolytic cell (a diaphragm electrolytic cell is composed of an anode region, a diaphragm and a cathode region arranged in parallel at intervals, and the diaphragm is a proton exchange membrane); the anolyte is a zinc sulfate-sulfuric acid-water solution containing ferrous ions and organic matter R, wherein the anolyte contains 6.2 g / L ferrous ions, 137.2 g / L zinc ions, 50.0 g / L sulfuric acid, 2000 mg / L total organic carbon of organic matter R, trace amounts of other metal ions (Cu 0.4 g / L, Cd 1 g / L, Ni 0.01 g / L, Co 0.02 g / L, As 0.5 mg / L, Sb 0.4 mg / L) and non-metal ions (F 3 20 mg / L, Cl 1200mg / L); the cathode electrolyte is a mixture of gelatin and sodium petroleum sulfonate RSO3Na added to a qualified zinc sulfate-sulfuric acid-water solution (the mass ratio of gelatin to sodium petroleum sulfonate RSO3Na is 5:1), and the addition amount of the mixture of gelatin and sodium petroleum sulfonate RSO3Na is 0.3kg / t based on the output Zn amount; the cathode electrolyte contains zinc ions 40g / L, H2SO490g / L, Mn2g / L and trace impurity ions, and the trace impurity ions include Cu≤2mg / L, Cd≤3mg / L, Ni≤2mg / L, Co≤2mg / L, As≤3mg / L, Sb≤0.5mg / L, Ge≤0.05mg / L, Fe≤20mg / L, F≤100mg / L, and Cl≤250mg / L; (2) The anode (lead-based alloy plate) and cathode (pure aluminum plate) were connected to the positive and negative electrodes of a DC power supply, respectively, and DC current was passed through the electrodeposition at a temperature of 30°C (the current density of the electrodeposition was 300A / m 2 ), the zinc ion content in the cathode electrolytic waste liquid at the end of electrolytic deposition is 1.5g / L lower than that in the cathode electrolyte at the starting point, so that the ferrous ions in the anode electrolyte of the anode area are oxidized to ferric ions, and the organic matter R is electro-oxidatively degraded to CO2 and H2O, and a zinc sulfate-sulfuric acid-water solution containing ferric ions is obtained (ferrous ions <10mg / L, total organic carbon of organic matter R <15mg / L), and high-purity zinc and cathode electrolytic waste liquid (the mass concentration ratio of H2SO4 to zinc ions is 2:1) are obtained at the cathode; (3) Regularly remove the anode with anode mud from the anode area of the diaphragm electrolytic cell (cycle is 7 days), remove the cathode with high-purity zinc deposited from the cathode area (cycle is 48 hours), and reinstall the anode after cleaning the anode mud and the cathode after stripping the zinc into the anode area and cathode area of the diaphragm electrolytic cell; (4) The zinc sulfate-sulfuric acid-water solution containing trivalent iron ions in the anode area is sent to the precipitation and iron removal process to precipitate iron from goethite; the cathode electrodeposition waste liquid with a volume fraction of 12% is sent to the hydrometallurgical zinc leaching process, and the remaining part is cooled and mixed with the qualified zinc sulfate-sulfuric acid-water solution in step (1) and then loaded into the cathode area of the diaphragm electrolytic cell as a new cathode electrolyte; The XRD pattern of the high purity zinc in this example is shown in Figure 2 ,from Figure 2 It can be seen that there is no impurity peak in the zinc sheet; Table 2 is the composition table of high-purity zinc.
[0034] Table 2 High purity zinc composition It can be seen from Table 2 that the purity of the high-purity zinc in this embodiment can reach 99.9992%; the ferrous ion oxidation rate in this embodiment is 99.8%, the organic matter degradation rate is 99.3%, the current efficiency is 91.3%, and the DC power consumption is 2530kW·h / t·Zn.
[0035] Example 3: A method for preparing high-purity zinc and synergistically electro-oxidizing ferrous ions and organic matter in a zinc sulfate solution, the specific steps are as follows: (1) The anode (lead-based alloy plate) and the anolyte are loaded into the anode area of a diaphragm electrolytic cell, and the cathode (pure aluminum plate) and the catholyte are loaded into the cathode area of a diaphragm electrolytic cell (the diaphragm electrolytic cell is composed of an anode area, a diaphragm and a cathode area arranged in parallel at intervals, and the diaphragm is a proton exchange membrane); the anolyte is a zinc sulfate-sulfuric acid-water solution containing ferrous ions and organic matter R, and the anolyte contains 25 g / L ferrous ions, 20.0 g / L zinc ions, 43 g / L sulfuric acid, 5000 mg / L total organic carbon of organic matter R, trace amounts of other metal ions (Cu 0.5 g / L, Cd 0.8 g / L, Ni 0.02 g / L, Co 0.01 g / L, As 0.4 mg / L, Sb 0.3 mg / L) and non-metal ions (F 560 mg / L, Cl 1 2.3g / L); the cathode electrolyte is a mixture of gelatin and sodium petroleum sulfonate RSO3Na added to a qualified zinc sulfate-sulfuric acid-water solution (the mass ratio of gelatin to sodium petroleum sulfonate RSO3Na is 8:1), and the addition amount of the mixture of gelatin and sodium petroleum sulfonate RSO3Na is 0.1kg / t based on the output Zn amount; the cathode electrolyte contains zinc ions 30g / L, H2SO4112g / L, Mn6g / L and trace impurity ions, and the trace impurity ions include Cu≤2mg / L, Cd≤3mg / L, Ni≤2mg / L, Co≤2mg / L, As≤3mg / L, Sb≤0.5mg / L, Ge≤0.05mg / L, Fe≤20mg / L, F≤100mg / L, and Cl≤250mg / L; (2) The anode (lead-based alloy plate) and cathode (pure aluminum plate) were connected to the positive and negative electrodes of a DC power supply, respectively, and DC current was passed through the electrodeposition at a temperature of 38°C (the current density of the electrodeposition was 400A / m 2 ), the zinc ion content in the cathode electrolysis waste liquid at the end of electrolysis is 3g / L lower than the zinc ion content in the cathode electrolyte at the starting point, so that the ferrous ions in the anode electrolyte of the anode area are electro-oxidized into trivalent ferrous ions, and the organic matter R is electro-oxidized and degraded into CO2 and H2O, and a zinc sulfate-sulfuric acid-water solution containing trivalent ferrous ions is obtained (ferrous ions <10mg / L, total organic carbon of organic matter R <15mg / L), and high-purity zinc and cathode electrolysis waste liquid (the mass concentration ratio of H2SO4 to zinc ions is 4:1) are obtained at the cathode; (3) Regularly remove the anode with anode mud from the anode area of the diaphragm electrolytic cell (cycle is 5 days), remove the cathode with high-purity zinc deposited from the cathode area (cycle is 36 hours), and reinstall the anode after cleaning the anode mud and the cathode after stripping the zinc into the anode area and cathode area of the diaphragm electrolytic cell; (4) The zinc sulfate-sulfuric acid-water solution containing trivalent iron ions in the anode area is sent to the precipitation and iron removal process to remove iron from goethite; the cathode electrodeposition waste liquid with a volume fraction of 25% is sent to the hydrometallurgical zinc leaching process, and the remaining part is cooled and mixed with the qualified zinc sulfate-sulfuric acid-water solution in step (1) and then loaded into the cathode area of the diaphragm electrolytic cell as a new cathode electrolyte; The SEM / EDS images of the high purity zinc in this example are shown in Figure 3 ,from Figure 3 It can be seen that SEM shows the hexagonal closest packing structure of zinc, and the EDS peaks are all characteristic peaks of zinc, and no other impurity peaks are seen; Table 3 is the composition table of high-purity zinc.
[0036] Table 3 High purity zinc composition It can be seen from Table 3 that the purity of the high-purity zinc in this embodiment can reach 99.9993%; the ferrous ion oxidation rate in this embodiment is 99.9%, the organic matter degradation rate is 99.8%, the current efficiency is 90.2%, and the DC power consumption is 2560kW·h / t·Zn.
[0037] Example 4: A method for preparing high-purity zinc and synergistically electro-oxidizing ferrous ions and organic matter in a zinc sulfate solution, the specific steps are as follows: (1) The anode (lead-based alloy plate) and the anolyte are loaded into the anode area of a diaphragm electrolytic cell, and the cathode (pure aluminum plate) and the cathode electrolyte are loaded into the cathode area of a diaphragm electrolytic cell (the diaphragm electrolytic cell is composed of an anode area, a diaphragm and a cathode area arranged in parallel at intervals, and the diaphragm is an anion exchange membrane); the anolyte is a zinc sulfate-sulfuric acid-water solution containing ferrous ions and organic matter R, and the anolyte contains 11.2 g / L ferrous ions, 150.8 g / L zinc ions, 26 g / L sulfuric acid, 430 mg / L total organic carbon of organic matter R, trace amounts of other metal ions (Cu 0.6 g / L, Cd 0.7 g / L, Ni 0.01 g / L, Co 0.03 g / L, As 0.6 mg / L, Sb 0.4 mg / L) and non-metal ions (F 1.2 g / L, Cl 3.7g / L); the cathode electrolyte is a mixture of gelatin and sodium petroleum sulfonate RSO3Na added to a qualified zinc sulfate-sulfuric acid-water solution (the mass ratio of gelatin to sodium petroleum sulfonate RSO3Na is 2:1), and the addition amount of the mixture of gelatin and sodium petroleum sulfonate RSO3Na is 0.03kg / t based on the output Zn amount; the cathode electrolyte contains zinc ions 53g / L, H2SO4 160g / L, Mn 5g / L and trace impurity ions, and the trace impurity ions include Cu≤2mg / L, Cd≤3mg / L, Ni≤2mg / L, Co≤2mg / L, As≤3mg / L, Sb≤0.5mg / L, Ge≤0.05mg / L, Fe≤20mg / L, F≤100mg / L, and Cl≤250mg / L; (2) The anode (lead-based alloy plate) and cathode (pure aluminum plate) were connected to the positive and negative electrodes of a DC power supply, respectively, and DC current was passed through at a temperature of 42°C for electrolysis (the current density of electrolysis was 510A / m 2 ), the zinc ion content in the cathode electrolysis waste liquid at the end of electrolysis is 9g / L lower than the zinc ion content in the cathode electrolyte at the starting point, so that the ferrous ions in the anode electrolyte of the anode area are electro-oxidized into trivalent ferrous ions, and the organic matter R is electro-oxidized and degraded into CO2 and H2O, to obtain a zinc sulfate-sulfuric acid-water solution containing trivalent iron (ferrous ions <10mg / L), the total organic carbon of organic matter R is <15mg / L, and high-purity zinc and cathode electrolysis waste liquid (the mass concentration ratio of H2SO4 to zinc ions is 5:1) are obtained at the cathode; (3) Regularly remove the anode with anode mud from the anode area of the diaphragm electrolytic cell (cycle is 4 days), remove the cathode with high-purity zinc deposited from the cathode area (cycle is 24 hours), and reinstall the anode after cleaning the anode mud and the cathode after stripping the zinc into the anode area and cathode area of the diaphragm electrolytic cell; (4) The zinc sulfate-sulfuric acid-water solution containing trivalent iron ions in the anode area is sent to the precipitation and iron removal process to remove iron from goethite; the cathode electrodeposition waste liquid with a volume fraction of 15% is sent to the wet zinc smelting leaching process, and the remaining part is cooled and mixed with the qualified zinc sulfate-sulfuric acid-water solution in step (1) and then loaded into the cathode area of the diaphragm electrolytic cell as a new cathode electrolyte; The infrared spectrum of zinc sulfate-sulfuric acid-water solution after degradation of organic matter R in this embodiment is shown in FIG. Figure 4 ,from Figure 4 It can be seen that the characteristic peaks of organic matter in the solution are weak; Table 4 is the composition table of high-purity zinc.
[0038] Table 4 High purity zinc composition It can be seen from Table 4 that the purity of the high-purity zinc in this embodiment can reach 99.9993%; the ferrous ion oxidation rate in this embodiment is 99.9%, the organic matter degradation rate is 97.8%, the current efficiency is 93.1%, and the DC power consumption is 2590kW·h / t·Zn.
[0039] The specific implementation modes of the present invention are described in detail above, but the present invention is not limited to the above implementation modes, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.
Claims
1. A method for preparing high-purity zinc and synergistically electro-oxidizing ferrous ions and organic matter in a zinc sulfate solution, characterized in that: The specific steps are as follows: (1) loading an anode and an anolyte into the anode region of a diaphragm electrolyzer, and loading a cathode and a catholyte into the cathode region of the diaphragm electrolyzer; the anolyte is a zinc sulfate-sulfuric acid-water solution containing ferrous ions and organic matter R, and the catholyte is a mixture of gelatin or bone glue and sodium petroleum sulfonate added to a qualified zinc sulfate-sulfuric acid-water solution; (2) connecting the anode and cathode to the positive and negative electrodes of a DC power supply respectively, passing DC current for electrolysis, so that the ferrous ions in the anolyte of the anode area are electro-oxidized into ferric ions, and the organic matter R is electro-oxidized and degraded into CO2 and H2O, thereby obtaining a zinc sulfate-sulfuric acid-water solution containing ferric ions, and obtaining high-purity zinc and cathode electrolysis waste liquid in the cathode area; (3) Regularly remove the anode with anode mud from the anode area of the diaphragm electrolytic cell, and remove the cathode with high-purity zinc deposited from the cathode area, and reinstall the anode after cleaning the anode mud and the cathode after stripping the zinc into the anode area and cathode area of the diaphragm electrolytic cell respectively; (4) The zinc sulfate-sulfuric acid-water solution containing trivalent iron ions in the anode area is sent to the precipitation and iron removal step for iron removal; the cathode electrodeposition waste liquid is sent to the wet zinc smelting leaching step, and the remaining part is cooled and mixed with the qualified zinc sulfate-sulfuric acid-water solution in step (1) and then loaded into the cathode area of the diaphragm electrolytic cell as a new cathode electrolyte.
2. The method for preparing high-purity zinc and co-electro-oxidizing ferrous ions and organic matter in zinc sulfate solution according to claim 1, characterized in that: The anode electrolyte in step (1) contains 0.02-25 g / L of ferrous ions, 20-180 g / L of zinc ions, 0.02-50 g / L of sulfuric acid, 30-5000 mg / L of total organic carbon of organic matter R, and trace amounts of other metal ions and non-metal ions.
3. The method for preparing high-purity zinc and co-electro-oxidizing ferrous ions and organic matter in zinc sulfate solution according to claim 1, characterized in that: Step (1) The cathode electrolyte contains 30-80 g / L zinc ions, 90-210 g / L H2SO4, 2-8 g / L Mn and trace impurity ions, wherein the trace impurity ions are Cu≤2 mg / L, Cd≤3 mg / L, Ni≤2 mg / L, Co≤2 mg / L, As≤3 mg / L, Sb≤0.5 mg / L, Ge≤0.05 mg / L, Fe≤20 mg / L, F≤100 mg / L and Cl≤250 mg / L; based on the output Zn amount, the addition amount of the mixture of gelatin or bone glue and sodium petroleum sulfonate is 0.03-0.5 kg / t.
4. The method for preparing high-purity zinc and co-electro-oxidizing ferrous ions and organic matter in zinc sulfate solution according to claim 1, characterized in that: Step (1) The anode is a lead-based alloy plate, and the cathode is a pure aluminum plate.
5. The method for preparing high-purity zinc and co-electro-oxidizing ferrous ions and organic matter in zinc sulfate solution according to claim 1, characterized in that: Step (1) The diaphragm electrolyzer consists of an anode region, a diaphragm and a cathode region which are arranged in parallel with each other, and the diaphragm is an anion exchange membrane or a proton exchange membrane.
6. The method for preparing high-purity zinc and co-electro-oxidizing ferrous ions and organic matter in zinc sulfate solution according to claim 1, characterized in that: Step (2) The current density of the electrolytic deposition is 300~600A / m 2 , temperature is 30~50℃, time is 24~48h.
7. The method for preparing high-purity zinc and co-electro-oxidizing ferrous ions and organic matter in zinc sulfate solution according to claim 1, characterized in that: In step (2), the ferrous ion in the zinc sulfate-sulfuric acid-water solution containing trivalent iron is less than 10 mg / L, the total organic carbon in the organic matter R is less than 15 mg / L, the mass concentration ratio of H2SO4 to zinc ion in the cathode electrolysis waste liquid is 2-5:1, and the zinc ion content in the cathode electrolysis waste liquid at the end point of electrolysis is 1.5-15 g / L lower than the zinc ion content in the cathode electrolyte at the starting point.
8. The method for preparing high-purity zinc and co-electro-oxidizing ferrous ions and organic matter in zinc sulfate solution according to claim 1, characterized in that: In step (3), the anode removal cycle is 4 to 7 days, and the cathode removal cycle is 24 to 48 hours.
9. The method for preparing high-purity zinc and co-electro-oxidizing ferrous ions and organic matter in zinc sulfate solution according to claim 1, characterized in that: The precipitation iron removal method in step (4) is hydrolysis iron precipitation or goethite iron precipitation.
10. The method for preparing high-purity zinc and co-electro-oxidizing ferrous ions and organic matter in zinc sulfate solution according to claim 1, characterized in that: The volume fraction of the cathode electrodeposition waste liquid sent to the hydrometallurgical zinc leaching process in step (4) is 8% to 25%.